Contesting Temporalities in a Runaway Slave Town: Mexico, 1769 to the Present - Amaral, Adela (Journal of Contemporary Archaeology, 2019)
This article follows various forms of colonial governmentality in Mexico and their legacies in the present. Beginning in the late eighteenth century and through reconstruction following the Mexican Revolution, state officials have attempted to construct the futures of residents of Amapa, a town founded by black runaway slaves. The article discusses how past and present townspeople have created and practiced distinct temporalities, incorporating the often-failed material and political potentials that were imagined for them.